Fused π-extended truxenes via a threefold borylation as the key step - Zhang, Gang; Rominger, Frank; Mastalerz, Michael (Chemistry - a European journal, 2016)
On the basis of a threefold borylated truxene, which is accessible in high yields by iridium-catalyzed borylation under CH-activation, fused π-extended truxenes have been synthesized by a two-step method of first Suzuki-Miyaura cross-coupling reaction and subsequent condensation reaction. The mild condensation method tolerates the presence of a variety of functional groups, such as nitro, fluoro, or carboxyl moieties. Furthermore, by using this approach, N- and S-heteroarene analogues become accessible for the first time, as well as larger structures that represent derivatives of precursors for fullerene C60 or buckybowls. The attached tert-butyl groups make all derivatives sufficiently soluble to allow full spectroscopic and electrochemical investigations. Postfunctionalization of selected derivatives for further synthetic applications of the compounds is also presented.